Comparing outcomes of robotic versus open mesorectal excision for rectal cancer. Issue 6 (18th January 2022) - Jimenez-Rodriguez, Rosa M; Flynn, Jessica; Patil, Sujata; Widmar, Maria; Quezada-Diaz, Felipe; Lynn, Patricio; Strombom, Paul; Temple, Larissa; Smith, Joshua J; Wei, Iris H; Pappou, Emmanouil P; Guillem, Jose G; et al.
Abstract: Background: The outcomes of robot-assisted mesorectal excision for rectal cancer, compared with open resection, have not been fully characterized. Methods: A retrospective analysis of pathologic, short-term, and long-term outcomes in patients with rectal adenocarcinoma who underwent total or tumour-specific mesorectal excision at a high-volume cancer centre between 2008 and 2017 was conducted. Outcomes after robotic and open surgery were compared on an intention-to-treat basis. Results: Out of 1048 resections performed, 1018 patients were reviewed, with 638 who underwent robotic surgery and 380 open surgery. Robotic surgery was converted to the open approach in 17 (2.7 per cent) patients. Patients who underwent robotic surgery were younger (median 54 (range 22–91) years versus median 58 (range 18–97) years; P < 0.001), had higher tumours (median 80 (range 0–150) mm from the anal verge versus median 70 (0–150) mm; P = 0.001), and were less likely to have received neoadjuvant therapy (64 per cent versus 73 per cent; P = 0.003). For patients who underwent a robotic total mesorectal excision, the operating time was longer (median 283.5 (range 117–712) min versus median 249 (range 70–661) min; P < 0.001). However, the rate of complications was lower (29 per cent versus 45 per cent; P < 0.001) and length of hospital stay was shorter (median 5 (range 1–32) days versus median 7 (range 0–137) days; P < 0.001). Median follow-up of survivors was 2.9 years. The proportion of patients with a positive circumferential resection margin did not differ between the groups, nor did the rate of local recurrence (robotic versus open: 3.7 per cent, 95 per cent c.i. 1.9 to 5.6 versus 2.8 per cent, 95 per cent c.i. 1.0 to 4.6; P = 0.400), systemic recurrence (robotic versus open: 11.7 per cent, 95 per cent c.i. 8.5 to 14.8 versus 13.0 per cent, 95 per cent c.i. 9.2 to 16.5; P = 0.300), or overall survival (robotic versus open: 97.8 per cent, 95 per cent c.i. 96.3 to 99.3 versus 93.5 per cent, 95 per cent c.i. 90.8 to 96.2; P = 0.050). The same results were documented in a subanalysis of 370 matched patients, including 185 who underwent robotic surgery and 185 open surgery, for the overall incidence of any postoperative complications, overall survival, disease-free survival, local recurrence, and systemic recurrence. Conclusion: In patients with rectal cancer who are candidates for curative resection, robotic mesorectal excision is associated with lower complication rates, shorter length of stay, and equivalent oncologic outcomes, compared with open mesorectal excision. Abstract : In patients with rectal cancer amenable to curative resection, robotic mesorectal excision was associated with lower complication rates, shorter length of stay, and equivalent oncologic outcomes, compared with open mesorectal excision. The results indicate that in high-volume centres, with institutional resources and support, the benefits of minimally invasive surgery can be extended to all rectal cancer patients without sacrificing oncological outcomes.